Ca2+-permeable TRPV1 pain receptor knockout rescues memory deficits and reduces amyloid-β and tau in a mouse model of Alzheimer's disease. (9th December 2019) - Kim, Juyong; Lee, Siyoung; Kim, Jaekyoon; Ham, Sangwoo; Park, Jung Han Yoon; Han, Seungbong; Jung, Yong-Keun; Shim, Insop; Han, Jung-Soo; Lee, Ki Won; Kim, Jiyoung
Abstract: The transient receptor potential vanilloid 1 (TRPV1) protein is a pain receptor that elicits a hot sensation when an organism eats the capsaicin of red chili peppers. This calcium (Ca 2+ )-permeable cation channel is mostly expressed in the peripheral nervous system sensory neurons but also in the central nervous system (e.g. hippocampus and cortex). Preclinical studies found that TRPV1 mediates behaviors associated with anxiety and depression. Loss of TRPV1 functionality increases expression of genes related to synaptic plasticity and neurogenesis. Thus, we hypothesized that TRPV1 deficiency may modulate Alzheimer's disease (AD). We generated a triple-transgenic AD mouse model (3xTg-AD +/+ ) with wild-type (TRPV1 +/+ ), hetero (TRPV1 +/− ) and knockout (TRPV1 −/− ) TRPV1 to investigate the role of TRPV1 in AD pathogenesis. We analyzed the animals' memory function, hippocampal Ca 2+ levels and amyloid-β (Aβ) and tau pathologies when they were 12 months old. We found that compared with 3xTg-AD −/− /TRPV1 +/+ mice, 3xTg-AD +/+ /TRPV1 +/+ mice had memory impairment and increased levels of hippocampal Ca 2+, Aβ and total and phosphorylated tau. However, 3xTg-AD +/+ /TRPV1 −/− mice had better memory function and lower levels of hippocampal Ca 2+, Aβ, tau and p-tau, compared with 3xTg-AD +/+ /TRPV1 +/+ mice. Examination of 3xTg-AD-derived primary neuronal cultures revealed that the intracellular Ca 2+ chelator BAPTA/AM and the TRPV1 antagonist capsazepine decreased the production of Aβ, tau and p-tau. Taken together, these results suggested that TRPV1 deficiency had anti-AD effects and promoted resilience to memory loss. These findings suggest that drugs or food components that modulate TRPV1 could be exploited as therapeutics to prevent or treat AD.